2010
DOI: 10.1177/1741143210383900
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Female Teachers’ Career Decisions: A Life History Study of 40 Women

Abstract: This article reports on some of the findings of a wider, life history study on the factors affecting the career decisions of 40 female secondary school teachers in England. By using life history interviews, it was possible to gain rich and nuanced insights into the complexity of factors influencing women's career decisions. While acknowledging the reality of constraints on women's lives and options, this article focuses on the women's perceptions of their own agency in their approach to career. A typology of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 15 publications
1
45
0
2
Order By: Relevance
“…It appeared that it was possible to align the responses to the model devised by Coleman (2002) summarising a career path, with all headteachers outlining their experiences identified as preparation, establishment, advancement or development, acquisition and performance. The typologies describing females and their approaches to their careers devised by Smith (2011a) has relevance, as previously noted in relation to "protestors". In addition, Hall's (1996: p. 47) reference to Evetts' (1990: p. 40) recognisable stages relating to both career and private life were identifiable.…”
Section: Women Researching Womenmentioning
confidence: 91%
See 2 more Smart Citations
“…It appeared that it was possible to align the responses to the model devised by Coleman (2002) summarising a career path, with all headteachers outlining their experiences identified as preparation, establishment, advancement or development, acquisition and performance. The typologies describing females and their approaches to their careers devised by Smith (2011a) has relevance, as previously noted in relation to "protestors". In addition, Hall's (1996: p. 47) reference to Evetts' (1990: p. 40) recognisable stages relating to both career and private life were identifiable.…”
Section: Women Researching Womenmentioning
confidence: 91%
“…In drawing conclusions (and based on the data from the wider investigations) through these established relationships and use of life history research, it appears that the respondents' experiences resonated with existing models in the field whether based on career pathways or emotional intelligence and life events, including the four noted in this paper (Evetts, 1990;Ciarrochi et al, 2001;Coleman, 2002;Smith, 2011a). In addition, is the notion of the usefulness of being researched in terms of professional and personal development as the respondents retrospectively discussed their career journeys.…”
Section: Female School Leadership Intelligent Use Of Emotions and LImentioning
confidence: 99%
See 1 more Smart Citation
“…This invisibility of gender equality issues reflects the normative acceptance of gender inequality in the highly feminized profession of teaching and masculine mode of senior management in the schooling sectors (Drudy 2008, Smith 2011, Lynch et al 2012. Given the earlier discussion of the gendered nature of participation in further education by students and staff, this is obviously still a pertinent social justice issue for further education to consider.…”
Section: Professionalism In Irish Further Educationmentioning
confidence: 99%
“…Researchers in the field of educational leadership have suggested that emotional intelligence of school leaders will have positive influence over the school operation, such as improving teachers' performance and satisfaction [8][9][10][11][12][13]. School leaders' high emotional intelligence, as is known as Goleman indicates, may enable teachers to feel that what they do is worthwhile and valued [14].…”
Section: Introductionmentioning
confidence: 99%